IL‐37: An anti‐inflammatory cytokine with antitumor functions. Issue 2 (22nd November 2018) - Mei, Yu; Liu, Haiyan
Abstract: Background: IL‐37 is a newly identified IL‐1 family cytokine. Unlike other members in IL‐1 family, IL‐37 has been demonstrated to be an anti‐inflammatory cytokine in many inflammatory and autoimmune diseases. IL‐37 is regarded as a dual‐function cytokine as both the extracellular and intracellular IL‐37 are biologically functional. Extracellular IL‐37 can bind to IL‐18Rα and IL‐1R8 to form a triple complex, regulating the downstream STAT3 and PTEN signaling. Intracellular IL‐37 can interact with Smad3, translocate into nucleus, and regulate downstream target gene expressions. Recently, the role of IL‐37 in tumor development has been extensively studied. Recent findings: IL‐37 has been found to play an antitumor role in various types of tumors, such as non‐small cell lung cancer, hepatocellular carcinoma, and renal cell carcinoma. Many mechanism studies have been carried out to elaborate the possible effects of IL‐37 on tumor growth, immune responses, and tumor angiogenesis. More importantly, the function of IL‐37 may be dependent on its concentration and receptor expression. It can form dimers at high concentrations to be inactivated, thus inhibiting its anti‐inflammatory function. We focused on the role of IL‐37 in various tumor types and provided the hypothesis regarding the underlying mechanisms. Conclusion: IL‐37 may affect tumor development through multiple mechanisms: (1) IL‐37 directly influences tumor cell viability; (2) IL‐37 regulates the immune response to promote the antitumor immunity; and (3) IL‐37 suppresses tumor angiogenesis in the tumor microenvironment. Future studies are warranted to further investigate the mechanisms of these multifaceted functions of IL‐37 in animal models and cancer patients.